Japanese management and the climate of the time - Kotabe, Masaaki (Asian business & management, 2020)
Management practices and orientation need to change when the climate of the time in which firms operate change. In the 1980s–early 1990s when the world enjoyed a broad economic growth on a global scale, Japanese management practices were once admired in awe around the world. Since the Japanese economy began to slip into a decade-long recessionary environment in the late 1990s, many Japanese firms experienced profit losses and the world’s admiration of Japanese management began to wane. This article explores how and why, and offers broader implications to management practices in general.